Fitur Bahasa Perempuan pada Gelar Wicara Kiki Saputri: “Roasting itu Mereka yang Minta” dalam Kanal Mata Najwa (Perspektif Robin Lakoff) - Firmansyah, Muhammad Rio (Kajian Bahasa dan Sastra (KABASTRA), 2023)
The use of woman language has distinctive characteristics that are different from the language used by man both in reality in life and in cyberspace. As for the content of the speech title on Najwa Sihab's Youtube channel, a woman speaker named Kiki Saputri is a representation of woman's language. The research method uses descriptive qualitative. The data such as words, phrases, clauses, and sentences that indicate woman language features. The source of the data comes from impressions that focus on Kiki Saputri's words. Data collection techniques are carried out by reading notes. The intepretative data analysis technique is description of the researcher in the woman language features of Lakoff's perpective. The results showed that a woman guest star named Kiki used seven of ten language features which included lexical hedges founded 5 data, increased intonation 4 data, intensifier 3 data, use of language according to the rules of 3 data, empty adjectives, emphatic stress, and polite speech each founded 1 data.